Immunotherapy enhances the risk of tumor oxidative stress and metastasis in lung cancer with radiation pneumonitis - Jiao, Ruidi; Xu, Wenbo; Xu, Kunpeng; Zhang, Mingxia; Liu, Weilong; Jiang, Wei; Wang, Luhua (Frontiers in Immunology, 2025)
Radiation pneumonitis (RP) is a prevalent complication associated with lung cancer radiotherapy; nonetheless, its effects on lung cancer immunotherapy and the underlying biological mechanisms remain inadequately elucidated. Utilizing mouse models of RP and orthotopically lung cancer, we witnessed immunotherapy-enhanced liver metastasis of lung cancer within the context of RP, accompanied by increased neutrophil infiltration of the primary tumor. Analysis of metabolic adaptations driven by the inflammatory microenvironment during treatment revealed that RP and immunotherapy act synergistically to exacerbate lipid metabolic dysregulation and oxidative stress. Integrating clinical validation with single-cell RNA sequencing data from a multicenter lung adenocarcinoma cohort, we demonstrated that elevated oxidative stress scores within tumor tissue were significantly associated with both diminished response to immunotherapy and unfavorable clinical outcomes. These findings coincided with alterations in the tumor immune microenvironment, notably a marked increase in neutrophils and activated mast cells. This investigation highlights that RP is not merely a toxicity but an active modulator of the tumor-immune-metabolism landscape. By dissecting the RP-ICB-metabolism axis, we have elucidated a novel mechanism underlying immunotherapy resistance, offering new insights into the rational design of optimized radioimmunotherapy.